Penerapan Nilai-Nilai Roma 12:2 dalam Membentuk Spiritualitas Kristen di Era Kontemporer yang Relevan dan Kontekstual - Rosmawati Rosmawati; Angelicha Tangke Tasik; Delpianti Delpianti; Gita Sartiva Parinussa; Juan Fakkach Tulak Allo (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
In the digital era, Christians face significant challenges in maintaining an authentic spirituality amidst a continuous stream of information and the influence of popular culture that often contradicts biblical values. The command in Romans 12:2 to